2021
DOI: 10.3390/cancers13122916
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Assessment of MicroRNA Diagnostic, Prognostic, and Theranostic Value in Colorectal Cancer

Abstract: MiRNAs have recently become a subject of great interest within cancers and especially colorectal cancers in diagnosis, prognosis, and therapy decisions; herein we review the current literature focusing on miRNAs in colorectal cancers, and we discuss future challenges to use this tool on a daily clinical basis. In liquid biopsies, miRNAs seem easily accessible and can give important information toward each step of the management of colorectal cancers. However, it is now necessary to highlight the most sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 122 publications
0
9
0
Order By: Relevance
“…The target genes of many miRNAs are proto-oncogenes or tumor suppressor genes, and the abnormal expression of miRNAs is a common feature of tumorigenesis ( Al-Akhrass and Christou, 2021 ). We hope that the microRNA microarray can help us find a potential therapeutic approach for EGFR-positive CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The target genes of many miRNAs are proto-oncogenes or tumor suppressor genes, and the abnormal expression of miRNAs is a common feature of tumorigenesis ( Al-Akhrass and Christou, 2021 ). We hope that the microRNA microarray can help us find a potential therapeutic approach for EGFR-positive CRC.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are found in all tissues and play a function in every cell type [7]. A large number of studies in CRC have also revealed that microRNA expression profiles change remarkably between normal tissues and tumors, were associated with drug resistance, as well as possess diagnostic, prognostic, and theranostic values [8][9][10][11]. Moreover, microRNAs play dual roles as oncogenes and tumor suppressors, which is the key function in tumorigenesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of miRNA expression profiles have been demonstrated to offer at least the same potential for identifying biomarkers as profiling their mRNA or protein equivalents. The presence of miRNAs in serum and plasma has been consistently documented, and the use of miRNAs as minimally invasive biomarkers for the identification of colon cancer has shown promising results [ 10 ].…”
Section: Introductionmentioning
confidence: 99%